2020
DOI: 10.1038/s41598-020-65166-y
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin for Treatment-Seeking Alcohol Use Disorder patients with sleeping problems: A randomized clinical pilot trial

Abstract: A high percentage of subjects diagnosed with alcohol use disorder (AUD) suffer from sleeping difficulties. Lack of sleep could lead AUD patients to relapse or, sometimes, to suicide. Most of the currently prescribed medications to treat this complex problem retain a high risk of side effects and/or dependence. Therefore, the aim of the current clinical trial is to investigate the possibility of the use of a safer treatment, such as the natural health product melatonin, to treat alcohol-related sleeping problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…As melatonin can diffuse quickly through the blood-brain barrier, it is effectively used in the treatment of brain injuries [ 7 , 10 , 16 ]. Rapid eye-movement sleep-behavior disorder patients are managed by a combination treatment of melatonin and clonazepam [ [17] , [18] , [19] ]. The sensing of bacteria through Toll-like receptor-4, and regulation of bacteria through altered goblet cells and antimicrobial peptides, are all involved in the anticolitic effects of melatonin in inflammatory bowel disease [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…As melatonin can diffuse quickly through the blood-brain barrier, it is effectively used in the treatment of brain injuries [ 7 , 10 , 16 ]. Rapid eye-movement sleep-behavior disorder patients are managed by a combination treatment of melatonin and clonazepam [ [17] , [18] , [19] ]. The sensing of bacteria through Toll-like receptor-4, and regulation of bacteria through altered goblet cells and antimicrobial peptides, are all involved in the anticolitic effects of melatonin in inflammatory bowel disease [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The studies were classified as high risk of bias, low risk of bias, and unclear risk of bias. The risk of bias summary and graph was generated using the online tool Risk-of-bias VISualization (robvis; Luke McGuinness, Bristol Medical School, Bristol, Uk) [26] and the summary of studies is shown in Figures 1, 2 [18,21,22,[27][28][29][30][31][32][33][34][35].…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The included studies were conducted in eight different countries such as Denmark [27,28,34,35], Israel [18,31], Iran [32], USA [30], Canada [29], Argentina [21], Spain [33], and Finland [22]. Studies have been conducted on various substances of addiction including benzodiazepine [18,21,22,27,28,31,[33][34][35], alcohol [29], nicotine [36] and opioid [32]. The sample size of the included studies ranges from 12 to 92 subjects (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation